Childhood adversity and the risk of substance use and delinquency: The role of protective adult relationships. (January 2017) - Brown, Samantha M.; Shillington, Audrey M.
Abstract: Youth involved in the child welfare system experience multiple early adversities that can contribute to increased risk of substance use and delinquency. Although adverse childhood experiences (ACEs) have been associated with poorer behavioral outcomes among youth, less is known about the possible protective factors that may influence the relationship between early adversity and risk-taking behavior. This study examined whether protective adult relationships moderated the link between cumulative ACEs and substance use and delinquency after controlling for demographic characteristics in child welfare-involved youth. The sample included 1054 youth, ages 11–17, from the National Survey of Child and Adolescent Well-Being II who were in the first wave of data collection. Results showed that protective adult relationships moderated the relationship between ACEs and substance use, but not for delinquency. Specifically, under lower levels of protective adult relationships, cumulative ACEs related to increased substance use among youth. Implications for child welfare practices to target youths' support systems are discussed.